Disease course of lung oligometastatic colorectal cancer treated with stereotactic body radiotherapy - Nicosia, Luca; Cuccia, Francesco; Mazzola, Rosario; Ricchetti, Francesco; Figlia, Vanessa; Giaj-Levra, Niccolò; Rigo, Michele; Tomasini, Davide; Pasinetti, Nadia; Corradini, Stefanie; Ruggieri, Ruggero; Alongi, Filippo (Strahlentherapie und Onkologie, 2020)
Purpose: Stereotactic body radiotherapy (SBRT) or stereotactic ablative radiotherapy (SABR) has been shown to increase survival rates in oligometastatic disease (OMD), but local control of colorectal metastases remains poor. We aimed to explore the natural course of oligometastatic colorectal cancer and to investigate how SBRT of lung metastases can delay the progression to polymetastatic disease (PMD). Methods: 107 lung oligometastases in 38 patients were treated with SBRT at a single institution. The median number of treated lesions was 2 (range 1–5). Time to PMD (ttPMD) was defined as the time from SBRT to the occurrence of >5 new metastases. Genetic biomarkers such as EGFR, KRAS, NRAS, BRAF, and microsatellite instability were investigated as predictive factors for response rates. Results: Median follow-up was 28 months. At median follow-up, 7 patients were free from disease and 31 had progression: 18 patients had sequential oligometastatic disease (SOMD) and 13 polymetastatic progression. All SOMD cases received a second SBRT course. Median progression-free survival (PFS) was 7 months (range 4–9 months); median ttPMD was 25.8 months (range 12–39 months) with 1‑ and 2‑year PFS rates of 62.5% and 53.4%, respectively. 1‑ and 2‑year local PFS (LPFS) rates were 91.5% and 80%, respectively. At univariate analysis, BRAF wildtype correlated with better LPFS (p = 0.003), SOMD after primary SBRT was associated with longer cancer-specific survival (p = 0.031). Median overall survival (OS) was 39.5 months (range 26–64 months) and 2‑year OS was 71.1%. Conclusion: The present results support local ablative treatment of lung metastases using SBRT in oligometastatic colorectal cancer patients, as it can delay the transition to PMD. Patients who progressed as SOMD maintained a survival advantage compared to those who developed PMD.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Gastrointestinal cancer; Metatases directed therapy; Polymetastatic disease; SABR; Stereotactic ablative radiotherapy